A Model of the Configuration Process of HR Systems within Multinational Subsidiaries in Indonesia - Rupidara, Neil Semuel (International Research Journal of Business Studies, 2019)
This article develops an empirical model of the process through which human resource management (henceforth HR) systems within subsidiaries of multinational companies (MNCs) are constructed. It extends current models that had previously been developed. It is a second-order analysis that integrates research findings that had been previously published along with unpublished materials from the same research project. The research project applied different qualitative methods in data collection. Complementing a previous conceptual macro model of the configuration process of HR systems, this article adds on a micro-empirical model of the process. The model proposes that the adoption and enactment of new HR ideas that make up HR systems is initiated by the reconceptualization of corporate identity and facilitated by the connectivity of relevant HR actors that enables the flows of ideas from the outside into the firms. Five research propositions are finally proposed to be tested as a contribution for future research.